Factors Associated with the Interest of IUD Contraceptive Users in Kalirong Village, Kediri Regency - Flariza Vindra Assafa; Lumastari Ajeng (Journal Of Nursing Practice, 2026)
Background: Population growth in Tarokan Village, Kediri, increased by 0.77% in 2021–2022 and 0.73% in 2022–2023, driven by a decline in contraceptive use. The largest decline occurred in IUD use, which fell from 46 in 2022 to 36 in 2023. Purpose: To identify factors influencing IUD contraceptive acceptors’ interest in Kalirong Village, Kediri. Methods: This study used a cross-sectional analytical survey of 82 PUS mothers aged >21–<35 years with >1 child, selected using simple random sampling. Data were collected via a questionnaire and analyzed using the chi-square test with a significance level of p = 0.1. Results: There was a significant association between the knowledge of postpartum mothers in Kalirong Village and their interest in IUD use (p = 0.000 < 0.1), whereas spousal support was not associated (p = 0.784 > 0.1). An analysis of parity was not performed because all respondents had the same parity. Conclusion: Knowledge is the dominant factor influencing interest in IUD use. Conclusion: Comprehensive education and counseling are essential to increase family planning participation, as women's knowledge significantly influences their interest in using an IUD, whereas spousal support and parity show no significant effect.